1987
DOI: 10.1111/j.1651-2227.1987.tb10457.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Cerebrospinal Fluid Sialic Acid Concentration in Children with Central Nervous System Leukemia

Abstract: We studied sialic acid in the cerebrospinal fluid (CSF) of 52 children with leukemia and 51 children with non-leukemic diseases. The CSF sialic acid concentration in the children with central nervous system (CNS) leukemia was significantly higher than that in the children with acute lymphoblastic leukemia without CNS involvement, acute non-lymphocytic leukemia without CNS involvement, non-hemopoietic diseases, non-suppurative meningitis, epilepsy, and other neurologic diseases. Serial determinations revealed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…However, the most accurate indicator of CSF dissemination of leukemia is still under dispute. Asami et al [27] observed a more rapid and marked decline in the CSF sialic acid level than in font after intrathecal therapy, and therefore suggested that sialic acid is a more sensitive and specific marker for leukemic CNS involvement.…”
Section: Cns Leukemiamentioning
confidence: 99%
“…However, the most accurate indicator of CSF dissemination of leukemia is still under dispute. Asami et al [27] observed a more rapid and marked decline in the CSF sialic acid level than in font after intrathecal therapy, and therefore suggested that sialic acid is a more sensitive and specific marker for leukemic CNS involvement.…”
Section: Cns Leukemiamentioning
confidence: 99%
“…Changes in CSF SA metabolites have been described in several diseases [3,[6][7][8]15]. Moreover, in a yet unidentified neurometabolic disease increased FSA has been reported in CSF while FSA content was normal in the urine and fibroblasts of these patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…The non-significant differences of CSF free SA in tubercular meningitis are explained due to lack of neuraminidase enzyme in tubercle bacilli. The amount of SA in CSF may also be a good indicator of central nervous system leukaemia [7] and for brain tumours [8]. Changes in the metabolism of SA by tumour cells are characterized by aberrant glycosylation processes by tumour cells resulting in larger amounts of SA on their surface compared with normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…In Price's series of 10 autopsies on patients with proven CNS involvement, the CSF WBC and blast cells were normal during the preceding week in 5 patients (Price and Johnson, 1973). It has been suggested that the CSF sialic acid concentration might serve as an indicator of CNS leukemia (Asami et al, 1987). The prognostic value of measurements of CSF sialic acid, if any, remains to be determined.…”
Section: Discussionmentioning
confidence: 99%